AKTIVITAS ANTIBAKTERI FORMULASI KRIM EKSTRAK DAUN JAMBU AIR (Syzygium aqueum) TERHADAP BAKTERI Propionibacterium acnes - Suci, Panji Ratih; Hamidah S, Cikra Ikhda Nur; Legowo, Deni Budi; Pangestutik, Zuanta (As-Syifaa Jurnal Farmasi, 2024)
The skin is the outermost layer or tissue that covers the entire body and protects the body from external threats, especially bacteria that cause acne which is a skin problem because it is caused by gram-positive bacteria, namely Propionibacterium acnes. Guava leaves (Syzygium aqueum) are known to contain flavonoids, tannins, alkaloids, and saponins which have antibacterial effects. This study aims to determine the water guava leaf extract cream and its antibacterial activity against Propionibacterium acnes. This research method is laboratory experimental. Testing the quality of the formulation was carried out by testing the organoletic, spreadability, homogeneity test and PH test. Testing the antibacterial activity using diffusion by measuring the value of the diameter of the zone of inhibition. The results showed that the ethanol extract cream complied with the organoleptic, potency, dispersion, homogeneity and pH tests, and had antibacterial activity with a concentration of 30% with an inhibition zone of 32.2 ± 0.31